NAMES OF RURAL ESTATES IN SOUTHWESTERN ISTRIA - Lucia Miškulin Saletović; Ines Virč (Fluminensia: Journal for Philological Research, 2008)
The paper deals with the motivation in giving names to rural estates. The names of rural estates collected during on-site research conducted in southwestern Istria in September, October and November 2007 have been selected as corpus. The paper first provides an analysis of names of rural estates based on the onomastic category of the onym they contain and then the names of rural estates are classified into different groups depending on their motivation.